Рядом с Пушкиным: портреты кистью и пером - Соколов Вадим Дмитриевич (Паритет ЛТД, 1991)
Экземпляры: ф. 3 (20090918) / Инвентарный номер: 94852 / Цена: 20 / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: С 59 / ББК: 83.3(2Рос=Рус)1